Less poverty in Egypt? explorations of alternative pasts with lessons for the future - Lofgren, Hans (International Food Policy Research Institute, 2001)
In this paper, the impact of alternative development strategies on growth and poverty is assessed in an economywide framework, using Egypt as a case study. The analysis is guided by the following question: By pursuing a development strategy different from the one actually pursued since the late 1970s, could Egypt’s government significantly have improved the status of its poor? To address this question, a dynamic, recursive, Computable General Equilibrium (CGE) model is used to simulate Egypt’s economy for the period 1979-1997. The model is built around a Social Accounting Matrix (SAM) for 1979. The results indicate that pro-poor redistribution of land and human capital assets could have been a particularly effective tool had Egypt prioritized more strongly to improve the welfare of the poor and reduce inequalities. Such policies could have been implemented without any noticeable negative impact on growth or aggregate welfare. The results also suggest that, for Egypt, there was no contradiction between more rapid growth, largely a function of more rapid productivity growth, and improved welfare for the poor. The present analysis confirms the finding of earlier analyses that, compared to pro-manufacturing policies, pro-agricultural policies have a more positive impact on household welfare in general and the poor in particular. There is a significant synergy between a pro-agricultural shift in productivity growth, improved market access for agricultural exports, and reduced transactions costs in foreign trade.